ANALISIS HUBUNGAN TINGKAT SERANGAN HAMA BELALANG KEMBARA (LOCUSTA MIGRATORIA MANILENSIS MEYEN) DENGAN CURAH HUJAN(ANALYSIS ON INFESTATION OF LOCUSTA MIGRATORIA MANILENSIS MEYEN BASED ON RAINFALL DATA) - Yonny Koesmaryono; Hana F.T.; Yusmin . (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2005)
Rainfall has an important role in the incidence of insect pests infestation, such as of locust grasshopper (Locusta migratoria manilensis Meyen). There are some provinces experience of locust grasshopper infestation, i.e. South Sumatera, Lampung, West and East Nusa Tenggara, North and South Sulawesi, West and Central Kalimantan. Generally, cropping season period of April–September and October-March shows a difference influence on the infestation of locust grasshopper. Most of districts in the provinces indicated that locust infestation increases in October–March cropping season, except in South Sulawesi it increases in April–September period. The analysis of correlation between rainfall and locust infestation applied in various timelags. The timelag was determined correspond with the life stage of locust, i.e. egg–hatching–nymphal–early imago–mating–active imago stage. The life stage of locust most influenced by rainfall and correspond with feed availability were active imago stage (in 9 districts) and egg stage (in 6 districts). The increase of rainfall during egg stage tend to suppress the infestation of locust, while during active imago stage the influence of rainfall tend to increase the infestation. The influence of rainfall closely correlated to locust infestation occurs in OKU, Central and South Lampung, West and East Sumba and West Ketawang.